2016
DOI: 10.1111/resp.12847
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes is associated with a higher incidence of hospitalization for pulmonary embolism in Spain: Analysis of hospital discharge data during 2004–2013

Abstract: Background and objective: We compared the incidence and outcome of pulmonary embolism (PE) in individuals with and without type 2 diabetes mellitus (T2DM) in Spain during 2004-2013.Methods: The study was based on National Hospital Discharge Data, and the study population comprised patients hospitalized for PE. Annual incidence rates were classified according to T2DM status. In-hospital mortality (IHM), length of hospital stay (LOHS), comorbidities and use of diagnosis and therapeutic procedures were analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…11 33 34 The CMBD is periodically audited and the validity of the ‘diabetes diagnosis’ in hospital discharge reports has been demonstrated in the past 35–38. However, as a result of these audits, it is possible and desirable that accuracy of coding may have improved over time so this would affect the results of our investigation and must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…11 33 34 The CMBD is periodically audited and the validity of the ‘diabetes diagnosis’ in hospital discharge reports has been demonstrated in the past 35–38. However, as a result of these audits, it is possible and desirable that accuracy of coding may have improved over time so this would affect the results of our investigation and must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited and conflicting evidence regarding outcomes specifically in orthopedic patients. Some studies [7, 9, 10, 11] have reported a higher likelihood of poor outcomes among inpatients with diabetes, whilst others [12, 13] reported no increase in risk.…”
Section: Introductionmentioning
confidence: 99%
“…Our results document a significant increase in the number of comorbidities over time, consistent with findings of previous studies [ 14 , 28 ]. Among the comorbidities that significantly increased over time were hypertension, diabetes, obesity, cancer, and chronic kidney disease, some of which are known risk factors for PE [ 29 , 30 , 31 ]. Despite an increasing burden of comorbidities for PE patients, the LOHS improved over time in our study, as other authors have described [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%